The mammal collection (Mammalia) of the Zoological Museum of Uzhhorod National University - Kron, A.; Lugovoy, O.; Roshko, V.; Roshko, V.; Roshko, V. (Theriologia Ukrainica, 2019)
The mammal collection of the Zoological Museum of Uzhhorod University consists of more than 4 800 specimens of 125 mammal species of world fauna. Among them, 115 mammal species are displayed in the exhibition halls. The mammal collection of the Zoological Museum is kept in scientific repositories, while a part of specimens is represented in three exhibition halls (210 exhibits). The geographic origin of specimens in the museum’s collection covers all continents but Antarctica. Most of the species represented in the exhibition (34 or 29.6 %) belong to Rodentia, followed by species of Carnivora (28 or 24.4 %) and Artiodactyla (15 or 13.0 %). The most common species in the collection are rodents (Rodentia): common vole (Microtus arvalis) and striped field mouse (Apodemus agrarius), a total of 1422 specimens. The general systematic representativeness of the exhibited part of the collection of mammals of the Carpathian region is 80 species, which is 77.2 % of the total number of mammals of the Ukrainian part of the Carpathians. In a systematic regard, the mammal collection of the Zoological Museum includes specimens of 125 species of 14 orders of the world fauna (41.2 %), representing 44 families and 89 genera. The collection contains 38 species listed in the Red Data Book of Ukraine, most of them belong to Chiroptera (9 species), Rodentia (9 species), and Carnivora (8 species). All bat species are listed in the Red Data Book of Ukraine. There are 497 bat specimens in the Zoological Museum, 13 of which are displayed in the exhibition halls. The IUCN Red List of Threatened Species, which covers six categories of conservation status, is additionally noted. The rarest species having endangered status (Endangered, EN) are the Russian desman (Desmana moschata), Malayan tapir (Tapirus indicus), tiger (Panthera tigris), Caspian seal (Phoca caspica), barbary macaque (Macaca sylvanus), Asian elephant (Elephas maximus), and European rabbit (Oryctolagus cuniculus). Some other species are critically endangered (CR): Chinese pangolin (Manis pentadactyla), European mink (Mustela lutreola), saiga antelope (Saiga tatarica), and Bornean orangutan (Pongo pygmaeus). Колекція ссавців Зоологічного музею Ужгородського національного університету представлена більше 4800 екз., що відносяться до 125 видів ссавців фауни світу. 115 видів ссавців представлені в експозиційних залах зоомузею. Колекція зоомузею зберігається в наукових фондах, частина з якої представлена в трьох експозиційних залах загальною чисельністю 210 експонатів. В географічному плані експозиція представляє всі частини світу, крім Антарктики. Більша частина експозиційних видів, а саме, 34 (29,6 %) — це представники ряду гризуни (Rodentia), 28 (24,4 %) — хижі (Carnivora) та 15 (13,0 %) парнопалі (Artiodactyla). Найчисельнішими видами в зоомузеї є з ряду гризунів (Rodentia) полівка європейська (Microtus arvalis) та житник пасистий (Apodemus agrarius) число яких сягає 1422 особи. Ссавці фауни Карпат в експозиційній частині музею представлені 80 видами, що становить 77,2 % від загальної кількості видів ссавців, відомих для Українських Карпат. У систематичному плані колекції ссавців зоомузею складають представники 14 рядів з 34 світової фауни (що становить 41,2 %), 44 родини, 89 родів. У колекції зберігаються 38 видів, що занесені до Червоної книги України, більшість яких з ряду кажанів (Chiroptera) (14 видів), гризунів (Rodentia) (9 видів) та хижих (Carnivora) (8 видів). Усі види кажанів занесені до Червоної книги України. В зоологічному музеї представлено 497 зразків, 13 з них в експозиційних залах. Додатково відмічені види Червоної книги МСОП, яка охоплює шість категорій охоронного статусу. Найрідкіснішими серед них є ті, що перебуває під загрозою (Endangered, EN): хохуля руська (Desmana moschata), тапір чепрачний (Tapirus indicus), бенгальський тигр (Panthera tigris tigris), нерпа каспійська (Phoca caspica), макака лісовий (Macaca sylvanus), слон індійський (Elephas maximus), кріль європейський (Oryctolagus cuniculus) та ті, що перебувають під критичною загрозою (Critically Endangered, CR), зокрема: панголін п’ятипалий (Manis pentadactyla), норка європейська (Mustela lutreola), сайга (Saiga tatarica) та орангутанг (Pongo pygmaeus).